Faust [videorecording] - Arabov, I͡Uriĭ, 1954- (Kino Lorber, 2014)
Heinrich Faust desires enlightenment. He seeks to understand the very nature of life and how the world goes round. Driven by his thirst for knowledge, he unearths corpses and rummages in their guts in search of the soul. He soon meets the racketeer Mauricius, who takes him to the twilight zones of their small town. In a bath house, his attention is caught by the young Margarete, also known as "Gretchen". Later, the two new friends are entangled in a pub brawl, during which Faust accidentally kills Gretchen's brother. Faust becomes obsessed with Gretchen, who seems to embody the beauty of blooming life. He indulges himself in thinking that studying her would be reasonable as a part of his research about what makes all the difference between life and death.